The social and economic impacts of immigration detention facilities: a South Australian case study. Issue 2 (June 2013) - Every, Danielle; Whetton, Steve; Rainbird, Sophia; Halim, Suraya Abdul; Procter, Nicholas; Sebben, Bianca; Thompson, Kirrilly
Abstract : The negative attitudes fostered by political rhetoric against asylum seekers create significant problems when asylum seekers are housed within communities. Much of the community's opposition focuses on the perceived economic and social impacts of large numbers of asylum seekers. However, we currently lack research on the local economic and social impacts of asylum seekers. As a contribution to this evidence base our paper outlines a South Australian case study of the impact of a low security immigration detention facility on the local economy, health services and social cohesion. Our impact assessment found that community concerns were not borne out. There were increases in employment and local expenditure, no reduction in health care services or access, and tensions between residents subsided, as did initially strong reactions against the asylum seekers themselves. The minimal impacts were due to the government and community interventions such as seeking local contracts and providing onsite health services. This case study is used to provide some guidelines for other communities to effectively target the fears that matter most to the community – either through disseminating information that reduces fears and myths, or through planning and interventions that minimise negative impacts and enhance positive benefits. In this way, the arrival of asylum seekers can potentially become one that benefits all community members.